Adherence to, Invasion by, and Cytokine Production in Response to Serotype VIII Group B Streptococci - Mikamo, Hiroshige (American Society for Microbiology, 2004)
The adherence to and invasion of the human epithelial cell line A549 by group B streptococcus (GBS) serotype VIII strains were compared with those of serotype III strains by a conventional method and the dynamic in vitro attachment and invasion system. Twenty GBS strains, including nine vaginal isolates and one invasive isolate each of serotypes III and VIII, were used in the conventional attachment and invasion assay. Adherence to and invasion of A549 cells by serotype VIII GBS strains were significantly greater (P < 0.0001) than those by serotype III strains for both the invasive strain and vaginal isolates. Cytokine production by A549 cells following stimulation with GBS serotypes III and VIII or their purified capsular polysaccharides (CPS) was measured. Serotype III strains stimulated significantly greater tumor necrosis factor alpha (TNF-α) (P < 0.0001) and interleukin-10 (IL-10) (P < 0.05) production than did serotype VIII strains. IL-8 production in response to serotype VIII was significantly higher (P < 0.001) than that in response to serotype III. TNF-α, IL-8, and IL-10 production was greater in A549 cells infected with GBS than in the untreated control cells. TNF-α production was significantly greater (P < 0.005) after stimulation with purified GBS serotype III CPS than after stimulation with serotype VIII CPS, a result similar to that after stimulation with whole GBS. IL-12 production by A549 cells was observed only in response to infection with GBS serotype III, resulting in the possibility of a greater TH1 response in serotype III GBS. These results suggest differences in immune responses to infection with GBS serotypes III and VIII.